Nilai Budaya dalam Cerita Rakyat (Seni Barongan) di Kudus - Sunaisah Sunaisah; Iffatul Ulya Rosyadi; Farida Maulida; Mohammad Kanzunnudin (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to analyze the cultural value of the folklore of Barongan Kudus Art. This research was motivated by the lack of public knowledge of the values contained in barongan art. The method used is qualitative descriptive. The source of the data comes from a book entitled